ANALYZING TENTH-GRADE STUDENTS’ DIFFICULTIES ON WRITING DESCRIPTIVE TEXT AT SMAN 1 BAROS - Ruwaida, Salma Nafisatur; Meisya, Meisya; Fauziah, Khoirunnisa; Tsani, Rijal Abdillah; Handayani, Ika; Usman, Rini Khairunnisa (Peneliti.net, 2024)
The focus of this study was to investigate the difficulties that arise in producing descriptive text for grade X (tenth) students at SMAN 1 Baros Serang. The researchers employ a qualitative descriptive research approach. Data is gathered utilizing three research instruments: observation, interviews, and tests (students’ work). As research participants, 42 students from the X7 class of SMAN 1 Baros were employed. During data analysis, students' writing challenges are identified and divided into writing factors based on Jacobs' theory. Meanwhile, data collection, namely observation, was carried out by collecting tasks, field notes, photos, recordings, and papers. According to the findings, the three major writing difficulty aspects experienced by students are grammar, vocabulary, and mechanism. Students find grammar to be the most difficult aspect of writing a description text, while content is the easiest. According to the data, the factor causing students' difficulties in writing descriptive texts is that they have no much knowledge and any experience about learning English from their previous education, resulting in a lack of knowledge and mastery of vocabulary, as well as students' low motivation to learn English.